Evaluation of root canal morphology of human mandibular incisors in Yazd - Tabrizi-zadeh M. Assistant Professor; Farazi K. Dentist (Tehran University of Medical Sciences, 2003)
Statement of Problem: The main objective of endodontic therapy is chemomechanical cleansing of entire pulp cavity and its complete obturation with an inert material. During this procedure, the failure of detection and inadequate cleaning of a canal will result in failed endodontic therapy. Therefore, the dentist must have enough knowledge of root canal morphology to treat a tooth successfully."nAim: The aim of this study was to determine the number and type of root canals of mandibular incisor teeth."nMaterials and Methods: In order to do this in-vitro, descriptive study, 68 non-carious mandibular incisor teethj collected from different clinics in Yazd, were immersed in indian ink, decalcified and cleared."nResults: It was found that 55.9% of the teeth had two separate canals that in 5.5% of them, the canals"nmerged before' apical foramen. In 4.4% of these samples, two separate canals existed along the whole"nroot."nConclusion: Considering high percentage of two canals in lower mandibular incisors, during access preparation, more attempts in detection of the second canal, is emphasized.